2021
DOI: 10.4103/crst.crst_138_21
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine uptake and vaccine hesitancy in Indian patients with cancer

Abstract: Background: Patients with cancer are at a higher risk of severe forms of coronavirus disease 2019 (COVID-19) and mortality. Therefore, widespread COVID-19 vaccination is required to attain herd immunity. Objectives: We aimed to evaluate the uptake of the COVID-19 vaccine in Indian patients with cancer and to collect information regarding vaccine hesitancy and factors that contributed to vaccine hesitancy. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This issue can be related to the complications of cancer treatments and the weakening of the immune system in these people (16). The results of studies have shown that cancer patients were afraid of and unsure about getting vaccinated for coronavirus, which could be due to the rumors surrounding these vaccines (17,18). In this regard, it appears that doctors can play an effective role in assuring the patients about the vaccine and its complications and recommending vaccination based on the conditions of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…This issue can be related to the complications of cancer treatments and the weakening of the immune system in these people (16). The results of studies have shown that cancer patients were afraid of and unsure about getting vaccinated for coronavirus, which could be due to the rumors surrounding these vaccines (17,18). In this regard, it appears that doctors can play an effective role in assuring the patients about the vaccine and its complications and recommending vaccination based on the conditions of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that COVID-19 vaccination intentions and public reaction toward CAB vary substantially across countries (Edwards et al, 2021). Noronha et al (2021) indicated the need for systematic strategies for education and information dissemination about the COVID-19 vaccine's safety and efficacy measures. The Government of India's Ministry of Health and Family Welfare proposed guidelines on CAB which explained 15 behavioral initiatives to be implemented to mitigate transmission (Table A1.…”
Section: Motivation Of the Researchmentioning
confidence: 99%
“…Previous studies suggested that COVID-19 vaccination intentions and public reaction toward CAB vary substantially across countries (Edwards et al ., 2021). Noronha et al . (2021) indicated the need for systematic strategies for education and information dissemination about the COVID-19 vaccine's safety and efficacy measures.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with cancer are at higher risk of developing serious COVID-19 infections [47], especially patients with leukemia (ORa 12.2), non-Hodgkin's lymphoma (ORa 8.5) and lung cancer (ORa 7.7), associated with a higher risk of mortality (14.9%) [43][44][45]. Acceptance of vaccination has been uneven among patients, ranging from 90% (in China) [46], 66% (in Holland) [47] to less than 47% (in India) [48].…”
Section: Risk and Protective Factors For Psychological Distress Durin...mentioning
confidence: 99%